Economic Valuation of Fish Provision, Wastewater Treatment, and Coastal Protection in the Israeli Mediterranean Sea - Shiri Zemah-Shamir; Yoav Peled; Mordechai Shechter; Álvaro Israel; Eyal Ofir; Gideon Gal (Fishes, 2023)
While many current and potential uses of the Israeli Mediterranean Sea have clearly defined the economic value and apparent benefits to various stakeholders (e.g., energy and raw materials extraction and maritime traffic), the benefits of these local marine ecosystems are still severely underexplored and are not manifested in economic terms. Coupled with ongoing environmental deterioration such as overfishing, climate change, and biological invasion, the need for performing monetary valuations of the benefits derived from this ecosystem is clearly evident. In this study, we evaluated three marine and coastal ecosystem services, namely, food provisioning, wastewater treatment, and coastal protection, in order to better quantify and map their importance to society. Food provisioning was inspected through the fishing sector, and its benefits were analyzed using the bioeconomic model. The results recommend a reduction in fishing efforts to increase overall biomass levels of both local and invasive fish species. However, this may lead to an economic loss in fishery profits due to reduced catch levels. The economic valuation of wastewater treatment as an ecosystem service hint at possible thresholds governed by effluent volumes and environmental conditions, whereby exceedance of Good Environmental Status (GES) standards may lead to a reduction of ~25% in the potential benefit of this ecosystem service. Finally, this study proposes an engineering restoration solution for compromised intertidal abrasion platforms, with estimated costs and potential benefits for the conservation of at-risk areas. The annual economic value of this ecosystem service is NIS 65–209 million (EUR 16.2–52.2 million).